Complex mosaic of sexual dichromatism and monochromatism in Pacific robins results from both gains and losses of elaborate coloration. (16th April 2020) - Kearns, Anna M.; Joseph, Leo; Austin, Jeremy J.; Driskell, Amy C.; Omland, Kevin E.
Abstract : Pacific robins exhibit one of the most complex range‐wide mosaics of sexual dichromatism and monochromatism. The evolutionary origins of this geographic mosaic remain poorly understood despite long‐standing interest from ornithologists, and its influential role in the development of Ernst Mayr's theories on speciation and the 'Biological Species Concept'. One factor limiting our understanding of the evolution of sexual plumage variation in Pacific robins is a lack of well‐resolved taxon boundaries and phylogenetic relationships in the group. Here, we use primarily historical museum specimens to obtain dense sampling of mtDNA, nuclear DNA, plumage color and morphometrics from all named taxa in the radiation in order to infer taxon boundaries and relationships. We use these data to test hypotheses about colonization history, plumage evolution and reduced island dichromatism. Our data show that the Pacific robin radiation comprises four distinct lineages, which warrant recognition as separate species – the previously recognized Norfolk robin P. multicolor and red‐capped robin P. goodenovii, and two new species we propose to name: 'Solomon robin' P. polymorpha Mayr, 1934 for the populations on Solomon and Bougainville Islands, and 'Mayr's robin' P. pusilla Peale, 1848 (in honor of Ernst Mayr's detailed work on the southwest Pacific robins) for the populations on Vanuatu, Fiji and Samoa. Our data suggest that the common ancestor of the entire Pacific robin radiation was most likely sexually dichromatic and that the radiation‐wide mosaic of sexual plumage color arose via repeated losses of elaborate plumage in males and gains of elaborate plumage in females on separate islands.